2020
DOI: 10.1021/acs.biochem.0c00088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Kinase R by Epstein-Barr Virus EBER1 RNA

Abstract: Protein kinase R (PKR) is a key antiviral component of the innate immune pathway and is activated by viral double-stranded RNAs (dsRNAs). Adenovirus-associated RNA 1 (VAI) is an abundant, noncoding viral RNA that functions as a decoy by binding PKR but not inducing activation, thereby inhibiting the antiviral response. In VAI, coaxial stacking produces an extended helix that mediates high-affinity PKR binding but is too short to result in activation. Like adenovirus, Epstein-Barr virus produces high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“… 15 Similarly, adenovirus VAI RNA produces KD dimers but does not activate PKR. 16 Finally, inactivating mutations within the PKR dimer interface that disrupt key electrostatic and hydrogen-binding interactions fail to abolish KD dimerization. 15 Together, these observations demonstrate that dimerization is a necessary but not sufficient step for the activation of PKR and point to the existence of one or more inactive dimer configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Similarly, adenovirus VAI RNA produces KD dimers but does not activate PKR. 16 Finally, inactivating mutations within the PKR dimer interface that disrupt key electrostatic and hydrogen-binding interactions fail to abolish KD dimerization. 15 Together, these observations demonstrate that dimerization is a necessary but not sufficient step for the activation of PKR and point to the existence of one or more inactive dimer configurations.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified several RNAs that can bind two PKR monomers and induce kinase domain dimerization but nonetheless fail to activate. 15 , 16 Affinity cleavage measurements suggested that simultaneous binding of both dsRBDs occurs only on activating RNAs. 17 NMR data indicate that only the N-terminus of dsRBD2 interacts with a short, nonactivating dsRNA, but extensive interactions with dsRBD2 occur upon binding to a longer, activating sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recently it has been found that, upon stimulation in vitro, the Epstein-Barr virus (EBV)infected IgA+ B cells secreted Gd-IgA1 and that B cells and their IgA+ subpopulation in PBMCs of IgAN patients displayed a significantly higher frequency of EBV infection than did cells of the same phenotype from non-IgAN patients (39). Interestingly, a different study very recently showed that PKR is regulated by EBV RNA (40).…”
Section: Creb Activation By Phosphorilation Leads To Il-6 Incerase In...mentioning
confidence: 99%
“…Bacterial and viral RNA may effectively further activate the PKR/CREB/IL-6 pathway leading to an excess of IL-6 production.Moreover, recently has been found that, upon stimulation in vitro, the Epstein-Barr virus (EBV)infected IgA+ B cells secreted Gd-IgA1 and that B cells and their IgA+ subpopulation in PBMCs of IgAN patients displayed a significantly higher frequency of EBV infection than did cells of the same phenotype from non-IgAN patients(39). Interestingly, a different study very recently showed that PKR is regulated by EBV RNA(40). This kind of mechanism, driven by the epigenetic silencing of VTRNA2-1, may therefore explain both the high levels of IL-6, and infection involvement in the disease, and recent data showingmicrobiota involvment in IgAN (9) (41) (42).…”
mentioning
confidence: 99%
“…Notably, disruption of the essential central domain pseudoknot structure converts VA RNAI from an inhibitor into an efficient PKR activator [ 45 ]. Taken together, it is likely that a specific structural conformation of the VA RNAI-PKR complex rather than physical sequestering of PKR by VA RNAI is needed for PKR inhibition [ 12 , 45 , 46 , 65 ].…”
Section: Va Rnamentioning
confidence: 99%